PERAN CIVIL SOCIETY SEBAGAI PRESSURE GROUP DALAM PERUMUSAN KEBIJAKAN PUBLIK (Studi Pada Malang Corruption Watch [MCW]) - Dody Setyawan (Universitas Tribhuwana Tunggadewi, 2011)
he idea of ​​civil society is increasingly a place in Indonesian public discourse, especially in reformation and decentralization era. The active role of civil society is needed as an alternative channel of participation to pressure public interest in area. The active participation of civil society will determine the sustainability of a process (formulation) of policy, especially for APBD. Did the APBD formulation made ​​become product policy dedicated to the society interest or vice versa? The objectives of this study were: 1) to find out the extent of the role and position of NGOs of Malang Corruption Watch (MCW) in APBD formulation; 2) to find out the methods used and described NGOs of MCW as a pressure group in the formulation. It was expected that this research would be useful for people who care about society rights and struggle to comply them, with interference of government absolutely. This study used qualitative method through observation, interview, and documentation. For data analysis the researcher used interactive data analysis, model developed by Miles and Huberman (1992), which includes the process of data reduction, presentation, and conclusions. From the research done, it could be obtained conclusions, they were: 1) MCW had roles in pressuring government in order to take side the society interests; 2) the method used by MCW in carrying out its role covered advocate and public education.